The Cactus - Haywood, Sarah (Farmington Hills, Mich. : Large Print Press, a part of Gale, a Cengage Company, 2019)
Messy emotions don't fit into the equation of her perfectly ordered life. She has a flat that is ideal for one, a job that suits her passion for logic and an 'interpersonal arrangement' that provides cultural and other, more intimate, benefits. Confronted with the loss of her mother and the news that she is pregnant, Susan's greatest fear is realized: she is losing control. Enter Rob, the dubious, well-meaning friend of her brother. As Susan's due date nears and her dismantled world falls further apart, she finds an unlikely ally in Rob. She might have a chance to find real love, and learn to love herself, if she can figure out how to let go.
Keywords: Single women -- Fiction -- Conduct of life; Asperger's syndrome -- Fiction; Pregnancy -- Fiction; Mothers -- Fiction -- Death; New mothers -- Fiction; Life change events -- Fiction; Grief -- Fiction; Bereavement -- Fiction; Brothers and sisters -- Fiction; Large type books; Domestic fiction